Robust reflections. Issue 4 (4th July 2022) - Andrews, David; Field, Chris
Abstract: Two senior statisticians/data scientists reflect on the challenges arising from the analysis of increasingly complex data using robustness. They include some thoughts on the types of robust analysis that will be needed in the future, while cognizant of our very limited ability to successfully predict the future. Résumé: Dans cet article, deux éminents statisticiens/analystes de données réfléchissent aux défis découlant de l'analyse de données de plus en plus complexes utilisant la robustesse. Conscients de la capacité très limitée à prédire avec succès l'avenir, ils abordent la question des types d'analyse robuste qui seront nécessaires dans l'avenir.